Federated learning and privacy-preserving in healthcare AI - Lilhore, Umesh Kumar 1982-; Simaiya, Sarita 1986-; Poongodi, Manoharan 1988-; Dutt, Vishal (Advances in healthcare information systems and administration (AHISA) book series, 2024)
The use of artificial intelligence (AI) in data-driven medicine has revolutionized healthcare, presenting practitioners with unprecedented tools for diagnosis and personalized therapy. However, this progress comes with a critical concern: the security and privacy of sensitive patient data. As healthcare increasingly leans on AI, the need for robust solutions to safeguard patient information has become more pressing than ever.